2015
DOI: 10.1007/s40140-015-0122-9
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Principles of Cancer Biology: Does It Have Relevance to the Perioperative Period?

Abstract: Malignant tumors are characterized by their ability to metastasize, which is the main cause of cancer-related mortality. Besides intrinsic alternations in cancer cells, the tumor microenvironment plays a pivotal role in tumor growth and metastasis. Ample evidence suggests that the perioperative period and the excision of the primary tumor can promote the development of metastases and can influence long-term cancer patient outcomes. The role of cancer biology and its impact on the perioperative period are of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…factors, and to decrease systemic levels of antiangiogenic factors. [53][54][55][56] In addition, nervousness, fear, and anxiety prior to the operation, blood transfusion, anesthetics, and hypothermia in the intraoperative period, and postoperative pain could also generate a microenvironment that is conducive to proliferation, angiogenesis, and invasion, thus increasing the recurrence risk in cancer [53][54][55] and conceivably in endometriosis as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…factors, and to decrease systemic levels of antiangiogenic factors. [53][54][55][56] In addition, nervousness, fear, and anxiety prior to the operation, blood transfusion, anesthetics, and hypothermia in the intraoperative period, and postoperative pain could also generate a microenvironment that is conducive to proliferation, angiogenesis, and invasion, thus increasing the recurrence risk in cancer [53][54][55] and conceivably in endometriosis as well.…”
Section: Discussionmentioning
confidence: 99%
“…34,51 Extensive basic and clinical research have shown that tissue damage and the manipulations and excision/ablation of lesions and their vasculature during operation suppress cell-mediated immunity, leading to immune escape of micrometastatic disease, 52 and may conceivably increase the shedding of endometriotic cells into the blood and lymphatic circulations, to increase local and systemic levels of growth factors, and to decrease systemic levels of antiangiogenic factors. 53 56 In addition, nervousness, fear, and anxiety prior to the operation, blood transfusion, anesthetics, and hypothermia in the intraoperative period, and postoperative pain could also generate a microenvironment that is conducive to proliferation, angiogenesis, and invasion, thus increasing the recurrence risk in cancer 53 55 and conceivably in endometriosis as well.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, how to accurately assess the blood transfusion amount and blood transfusion type of patient during the perioperative period is a research hotspot in clinic. The traditional blood routine and coagulation function have a low detection mobility and their real-time monitoring ability is poor, thereby they cannot meet the clinical accurate judgment for the condition of patient's blood transfusion; TEG is the only effective method to continuously and dynamically monitor the process of blood coagulation when the blood transfusion amount is extremely low (19,20). Not only does it have a good monitoring effect on the changes in cells and plasma, but also have a clear judgment on the generation time of blood clots (21).…”
Section: Discussionmentioning
confidence: 99%
“…Cancer may arise due to different extrinsic and/or intrinsic causes that drive transformation through heterologous mechanisms often associated with a variety of genomic events, which can then lead to an even more diverse clinical presentation and course [1,2]. Cancer development often follows the same pathogenesis: starting from a single genetic event and leading to acquisition of additional genetic and epigenetic abnormalities, clonal evolution and plasticity (events that confer remarkable biological advantage over normal differentiated cellular elements, together with the ability to evolve, develop drug resistance and escape immune surveillance) [3,4]. One of the first attempts to explain cancer development, with regards to somatic (DNA) mutations, was the two-hit hypothesis proposed by Alfred Knudson in 1971, which posits that cancer development requires at least two mutations: one in a proto-oncogene, which then turns into an oncogene, and one in a tumor-suppressor gene [5].…”
Section: Introductionmentioning
confidence: 99%